Uso de conceitos das Ciências Sociais nas aulas de sociologia no ensino médio: proposta de uma sequência didática - Fonseca, Francisco Anarclebson do Rêgo (2022)
The challenges of Sociology Teaching in Brazilian Secondary Education occur on different levels. One of them is that the discipline has a theoretical and academic aspect and is taught by professors who, for the most part, do not have a compatible higher education. These aspects involve rethinking the approaches and resources used in teaching situations. Considering this, in this study a Didactic Sequence (DS) was elaborated with the concept of Cultural Industry, to support the teacher's work in the classroom. It is a strategy that intends to contribute to improve teaching and learning with regard to the operationalization of the Concept of Social Sciences, through data collected with High School Sociology teachers from the Ceará State Education Network. The investigation was methodologically guided by the Qualitative Research approach and the theoretical assumptions of content analysis (BENGTSSON, 2016; BARDIN, 2016; FRANCO, 2021). The SD was planned using the collected data and some principles of the way of thinking sociologically (BARREIRA, 2014) using the concepts as a tool (MEUCCI, 2009) from the didactic transcription of known knowledge, knowing how to teach and knowing taught (CHEVALLARD, 1991) . The SD of the Cultural Industry concept emerged from what we perceived in the questionnaires and interviews with the teachers of School Sociology, which were applied in a class of 1st year of High School of a public school in Fortaleza/CE, that is, in an environment formal educational. As a result of the implementation, it was observed that the developed SD contributed to the fulfillment of a more significant learning, allowing more clarity, with the objective of developing competences and abilities in the students (ZABALA, 1998).